Conflict between Customary Law and Islamic Law in the Postponement of Joint Property Distribution After Divorce - Seri Bahreni Riski; Misran Misran; Boihaqi bin Adnan; Nur Syahirah Mohammad Nasir (Yayasan Cendekia Gagayunan Indonesia, 2026)
The postponement of the distribution of joint property after divorce is still an ongoing socio-juridical problem and has an impact on weak legal certainty and the fulfillment of economic rights after divorce, especially for women. Although Indonesian positive law and Islamic law normatively regulate the division of common property, there is still a gap between legal norms and the practice of their implementation in a society based on customary law. This research fills the research gap in the form of a lack of empirical juridical studies on the postponement of the distribution of common property in the interaction between customary law, Islamic law, and state law in traditional societies. The purpose of this study is to analyze the causal factors, patterns, and legal implications of post-divorce joint property distribution, with an emphasis on the protection of economic rights. The method used is empirical juridical with a socio-legal approach, which is carried out through field research in Katimaju Village, Ketambe District, Southeast Aceh Regency, with in-depth interview techniques and document analysis. The results of the study show that the delay in the distribution of joint property is influenced by the strong customary norms, the dominance of the role of extended families and traditional leaders, and the prevalence of unregistered marriages, which has implications for legal uncertainty and weak economic protection for women. The novelty of this research lies in an integrative analysis between normative legal frameworks and local social practices that reveal structural injustices in customary dispute resolution mechanisms. Based on these findings, this study recommends that the settlement of the distribution of joint property after divorce be required through a legal mechanism that has binding power by involving the Religious Court as the main authority, accompanied by the reformulation of customary dispute resolution mechanisms to be in harmony with Islamic law and state law, increasing the legalization of marriage through marriage registration, and strengthening community-based legal education to ensure legal certainty. protect women's economic rights, and realize substantive justice in indigenous peoples.